Removal of palladium ions from aqueous systems by chemically modified cysteine carbon powder - Abiman, P.; Wildgoos, G.G.; Crossley, A.; Compton, R.G. (The Royal Society of Chemistry, 2008)
l-Cysteine methyl ester modified graphite powder (Cyscarbon) was used as a material to remove palladium ions from aqueous media. Cheap graphite powders (2-20 μm in diameter) were surface functionalised with l-cysteine methyl ester. The removal of Pd(ii) ions was studied as a function of concentration of Pd(ii) ions, contact time with modified carbon and amount of modified carbon used. Determination of palladium ions was performed by adsorptive stripping voltammetry using a mercury nanodroplet array modified glassy carbon electrode. Dimethylglyoxime (DMG) was used as chelating agent for palladium. It was found that 1 g of Cyscarbon takes up 60 μM palladium ions from 25 mL of 100 μM palladium ion samples whilst the recovery experiment carried out by stirring the palladium-Cyscarbon with DMG gave a yield of 45% (optimised).